2013
DOI: 10.4334/jkci.2013.25.1.063
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Behavior of Hybrid Truss Bridge according to Connection Systems

Abstract: HTB (hybrid truss bridge) steel truss webs instead of concrete webs in prestressed box girder bridges has been widely used in, because of its structural benefit such as relatively less self-weight and good aesthetics due to open web structure. Since the core technology of this bridge is the connection system between concrete slabs and steel truss members, several connection systems were proposed and experimentally evaluated. Also, the selected joint system was applied to the real bride design and construction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…정광회 등(2013)은 기존 연구를 통해 복합트러스교에 대한 비틀림 모멘트 산정식을 계산하고 실험적 연구를 통해 격점구조별 비틀림 성능을 분석하였다. 13) Fig. 2의 복부파형강판 교량과 같이 종방향 단면이 일정하지 않은 복합 트러스교는 비틀림모멘트를 계산함에 있어, 일정한 간격으로 배치된 복부 트러스 부재를 연속된 복부로 환 산하고, 상 ․ 하 콘크리트 슬래브와 복부로 둘러싸인 폐단…”
Section: 서 론 1)unclassified
“…정광회 등(2013)은 기존 연구를 통해 복합트러스교에 대한 비틀림 모멘트 산정식을 계산하고 실험적 연구를 통해 격점구조별 비틀림 성능을 분석하였다. 13) Fig. 2의 복부파형강판 교량과 같이 종방향 단면이 일정하지 않은 복합 트러스교는 비틀림모멘트를 계산함에 있어, 일정한 간격으로 배치된 복부 트러스 부재를 연속된 복부로 환 산하고, 상 ․ 하 콘크리트 슬래브와 복부로 둘러싸인 폐단…”
Section: 서 론 1)unclassified
“…The steel-concrete connection joint is considered the most important part of hybrid truss bridges, transferring the load between the concrete chord and steel truss web [11,17,[20][21][22][23][24]. Therefore, some experimental and analytical studies on such joint structures have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanical behavior was affected by the form of welding [29]. To reduce welding during construction, Jung et al [1,11,13,20,22] proposed a new connection joint composed of connection plates and a connection bolt. Furthermore, experimental and numerical investigations were carried out on this new connection system and HTB girders to clarify the structural capacity, fatigue capacity and torsional behavior.…”
Section: Introductionmentioning
confidence: 99%
“…2. (Jung et al 2013b) In EHT, the center of the concrete deck is in alignment with the centerline of the steel truss member such that the eccentric moment would be minimized as shown in Fig. 2(a).…”
Section: Load Transfer Mechanisms At the Connection Jointmentioning
confidence: 99%